Improvement of writing proficiency through creation of homogeneous groups in the classroom (2000)
Our interest in students’ writing in the second language (English) encouraged us to carry out research in the classroom, taking homogeneous group and mixing it with new activities to provide alternatives in writing. We found a lot of theory about writing skills which did not take into account students’ problems such as adolescence, likes, environment and their attitude toward English. From these elements we developed a research project divided into two cycles. The first cycle confirmed a problem and the second one was used to provide possible solutions to the problem (writing proficiency), always taking into account our students as the main performers in our research.